Lipids at the plant–animal interface: a stable isotope labelling method to evaluate the assimilation of essential fatty acids in the marine copepod Calanus finmarchicus - Helenius, Laura; Budge, Suzanne; Duerksen, Steven; Devred, Emmanuel; Johnson, Catherine L (Journal of Plankton Research, 2019)
Abstract Linking production, transfer and subsequent bioavailability of nutritionally significant matter from phytoplankton to higher trophic levels is a fundamental aspect in understanding marine food webs. The plant–animal interface is of interest because of the highly variable transfer between producers and consumers, and the myriad of factors that influence it. Essential fatty acids (EFAs) are dietary nutrients that are necessary for normal function in all consumers, yet it remains unclear how efficiently they are transferred through marine food webs. We introduced a 13C-labelled carbon source to the cryptophyte Rhodomonas salina to quantify primary production of two omega-3 long-chain polyunsaturated fatty acids (PUFAs), eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA). We investigated transfer and assimilation efficiencies of these EFAs from phytoplankton to the calanoid copepod Calanus finmarchicus in an 8-day feeding experiment. We found low production of both EFAs in R. salina. Assimilation efficiencies of both EFAs ranged from 5 to 15% throughout the experiment, remaining slightly higher on average for DHA. This was mirrored in more efficient trophic transfer of DHA (up to 28%, compared to 13% for EPA). These results add to previously scarce experiments empirically quantifying the assimilation and transfer efficiency of EFAs in a basic marine planktonic food chain.